Single-cell DNA from West Greenland marine sediments suggests presence of Protoperidinium tricingulatum in the Arctic - Luostarinen, Tiia; Ribeiro, Sofia; Zimmermann, Heike; Kvorning, Anna Bang; Heikkilä, Maija (Journal of Eukaryotic Microbiology, 2023)
Peer reviewed